Economic losses reduction through the implementation of statistical process control: case study in the process of medical accounts in a technology company (2019)
Statistical process control (SPC) is one of the most important tools for process continuous improvement. Its usefulness lies on the fact that it helps in the identification of causes of variation in the process. This allows the decision maker to take the corresponding actions in such a way that the improvement of the associated indicators is achieved. In this particular case, the methodology of the SPC was used to intervene a process of verification and collection of medical accounts by a technology company. The errors in these accounts can cause that the health companies do not pay the correct amount to hospitals. This situation may affect the service to users or that the health companies have economic losses. The implementation of the statistical process control (SPC) had a big impact in the identification of problems, stabilization of the process, and improvement of satisfaction and reduction of quality costs.